The Alleged 'Beth David' in the Mesha Stele: The Case Against It. (3rd July 2019) - Na'aman, Nadav
Abstract: The article examines the validity of the rendering בתדוד in Line 31 of the Mesha Stele ("And as for Ḥāwrônên, בתדוד dwelt in it"). Examination of the corpus of West Semitic royal inscriptions reveals only one parallel to a kingdom's name that functions as the operative agent in a royal inscription. Evidently, the suggested restoration בתדוד that is governed by the verb ישב in the badly eroded Line 31 should be rejected. Rather, the best proposal thus far for the controversial line is the recently posited restoration, "And as for Ḥāwrônên, there dwelt Ba[lak]".